2012
DOI: 10.7314/apjcp.2012.13.8.3669
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Xenotropic Murine Leukemia Virus and its R426Q Polymorphism in Patients with Prostate Cancer in Kerman, Southeast of Iran

Abstract: A role for the xenotropic murine leukemia virus (XMRV) in prostate cancer development has been postulated. To answer questions regarding the prevalence of XMRV in Iranian patients with prostate cancer and its association with the RNASEL R462Q polymorphism, we here investigated a series of cases in Kerman, in the Southeast of Iran, and sought to verify the association with the R462Q using Real Time PCR Method. Prostate tissue specimens of 200 patients with prostate cancer were genotyped for R462Q by real time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…In addition, studies failing to detect XMRV or related MLVs in prostate cancer and CFS patients outnumber the studies confirming the original findings (Korn et al, 2012;Mi et al, 2012;Paolucci et al, 2012;Rezaei, Hearps et al, 2013). In a study the presence of XMRV was detected among some patients with prostate cancer in the Iran, but did not find any correlation between XMRV infection and various clinical pathological parameters of prostate cancer (Reza, Fahimeh et al, 2012).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In addition, studies failing to detect XMRV or related MLVs in prostate cancer and CFS patients outnumber the studies confirming the original findings (Korn et al, 2012;Mi et al, 2012;Paolucci et al, 2012;Rezaei, Hearps et al, 2013). In a study the presence of XMRV was detected among some patients with prostate cancer in the Iran, but did not find any correlation between XMRV infection and various clinical pathological parameters of prostate cancer (Reza, Fahimeh et al, 2012).…”
Section: Discussionmentioning
confidence: 53%
“…Moreover neutralizing antibodies for XMRV were identified in 11 of 40 patients with prostate cancer and XMRV sequences were confirmed in five of 11 by nested PCR and fluorescence in situ hybridization (Arnold et al, 2010;Switzer et al, 2011). Recently a study reported that, XMRV was detectable in some patients with prostate cancer in Kerman, southeast of Iran (Reza et al, 2012). In contrast, in other studies have been found very low or no XMRV prevalence in prostate cancers in Europe (Germany, and the Netherlands) and USA using only RT-PCR (Fischer et al, 2008;Hohn et al, 2009;Aloia et al, 2010;Silverman et al, 2010;Sakuma et al, 2011;Sfanos, 2011;Stieler et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…It was suggested that XMRV prevalence in patients with CFS and patients with prostate cancer carrying a homozygous R462Q mutation in the RNaseL gene is 67% and 40%, respectively. [ 2 8 16 24 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…The primers previously described were used for molecular detection via RT-PCR technique for these two targets [ Table 1 ]. [ 24 25 ] A total volume of 25 μL reaction mixture consisted of a 5-μM concentration of cDNA samples or controls, a deoxyribonucleoside triphosphates (dNTPs) mix (Fermentas, Germany) with equal concentrations of each of the four dNTPs at a 1mM concentration, each of forward and reverse primers at 1 μM concentration, MgCl 2 solution (Fermentas) at 1 μM concentration, 2.5 μM concentration PCR buffer 10x (Fermentas), and 0.5 units/μL concentration of Taq DNA polymerase (Fermentas), and sterilized distilled water was added to round out the total volume.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…In agreement with recent studies that also showed general absence of XMRV or detection of it in a small subset of cases ( 23 - 27 ), XMRV was not detected in our study groups, suggesting that the distribution of XMRV may vary in different geographic regions ( 24 ). In a study in Kerman, Iran, XMRV was detected only in 4% of patients with prostate cancer ( 31 ). The lack of XMRV in the present study may be due to population heterogeneity, as these patients referred to Sina Hospital from all over the country.…”
Section: Discussionmentioning
confidence: 99%